Pengaruh Media Wordwall Terhadap Hasil Belajar Matematika Materi Bangun Datar Kelas V di SDN Pekayon Jaya IV - Rengganis, Farida Atasya; Ninawati, Mimin (LPPM Institut Pendidikan Nusantara Global, 2025)
The learning process requires supportive instructional tools to achieve optimal student learning outcomes. One of the essential components is instructional media that is not only engaging and interactive but also meaningful for students. The use of such media is considered effective in assisting teachers in delivering learning material more efficiently. This study focuses on examining the effect of Wordwall media on students’ learning outcomes at the elementary school level. The research employed a quasi-experimental method using a post-test only control group design. The subjects of this study were fifth-grade students at SDN Pekayon Jaya IV, selected through a non-probability sampling technique. Data collection was carried out through a post-test in the form of essay questions. The results revealed that the learning outcomes of students in the experimental class, which utilized Wordwall media, were higher than those in the control class that did not use the media. Based on these findings, it can be concluded that the use of Wordwall media has a positive influence on mathematics learning outcomes of fifth-grade students at SDN Pekayon Jaya IV.